Hedonisme di Kalangan Mahasiswa: Eksplorasi Atas Pencarian Kenikmatan Instan Dalam Lingkungan Pendidikan Tinggi - Fatin oktariani, Nazwa; Mahesa Candra Kerti, Fariq; Aulia Rahmani, Nisrina; Zalva, Syahbila; Hamidah, Siti (JURNAL SOSIAL Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Hedonism is the teaching or view that pleasure or enjoyment is the goal of human life and actions. The meaning of hedonism has shifted over time. Hedonism is currently synonymous with luxury and an excessive lifestyle, and tends to lead to consumer behavior. People who behave hedonistically are usually called hedonists, where they always maximize their feelings of pleasure if they want something to the maximum. Hedonistic behavior can be caused by several factors, namely internal and external. Hedonistic behavior has been found in many places and almost all groups have experienced it and even experienced it. hedonism can be said that the goal of hedonism is the aim of living naturally with pleasure for humans. Not a few people who have a hedonistic lifestyle will do things that are sometimes beyond reason in order to justify any means, whether it is hurting or harming other people, even those closest to them. This research aims to find out the extent of the factors and influences of hedonistic behavior among teenagers collected from several articles that have been published. The method used for this research is a Literature Review which collects several articles that have been published. Hedonism does not occur in a certain place, but is a lifestyle that can be adopted by several people and in several circles, one of which is teenagers. Because during the character formation period it can have a big influence on its adherents